2001
DOI: 10.1128/cdli.8.1.178-180.2001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neutrophil Function in Patients with Septic Shock: Comparison of Methods

Abstract: Patients with septic shock are shown to have decreased neutrophil phagocytic function by multiple assays, and their assessment by whole-blood assays (fluorescence-activated cell sorter analysis) correlates with assays requiring isolated neutrophils (microscopic and spectrophotometric assays). For patients with similar underlying conditions but without septic shock, this correlation does not occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, iron chelation has inhibitory effects on the replication of intra-macrophage Salmonella in iron starvation models based on another iron chelator, deferasirox 33 35 . We propose here that reduction of the available iron specifically in the SCV attenuates the production of hydroxyl radicals, which accounts for the capacity of these cells to limit intra-macrophage Salmonella growth 36 (Supplementary Fig. 14 ).…”
Section: Discussionmentioning
confidence: 91%
“…However, iron chelation has inhibitory effects on the replication of intra-macrophage Salmonella in iron starvation models based on another iron chelator, deferasirox 33 35 . We propose here that reduction of the available iron specifically in the SCV attenuates the production of hydroxyl radicals, which accounts for the capacity of these cells to limit intra-macrophage Salmonella growth 36 (Supplementary Fig. 14 ).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, immature neutrophils produced significantly lower levels of ROS in response to PMA and E. coli than mature granulocytes, possibly due to the immaturity of the nicotinamide adenine dinucleotide phosphate oxidase or of the enzymatic pathway of H 2 O 2 production (superoxide dismutase). Interestingly, it was shown that efficiency in bacterial killing was positively correlated with levels in ROS production is septic neutrophils (41). S. aureus induced low levels of H 2 O 2 in neutrophils, and no significant difference was observed between the different neutrophil subsets.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, conflicting findings in severe infection could be due to variability in the total numbers of underactive immature neutrophils compared with activated fully-differentiated neutrophils [ 158 , 159 ]. Despite displaying an activated basal state, the mature neutrophils from patients with severe infection do not generate ROS to the same extent as healthy neutrophils following ex vivo stimulation [ 160 ]. The effect of vitamin C supplementation on phagocytosis, oxidant generation, and microbial killing by leukocytes from septic patients has not yet been explored.…”
Section: Vitamin C and Leukocyte Functionmentioning
confidence: 99%